ALTERNATIF PENGGUNAAN SILIKA BENTONIT SEBAGAI PENGGANTI FENOL-KLOROFORM-ISOAMIL ALKOHOL DALAM EKSTRAKSI DNA SECARA LANGSUNG DARI TANAH HUTAN MANGROVE - Khisan Qamariya; Wahyu Dwijani Sulihingtyas; I Nengah Wirajana (Jurnal Kimia (Journal of Chemistry), 2016)
Research on comparing the metagenomic DNA extraction from mangrove forest soil with phenol-chloroform-isoamyl alcohol and with silica bentonite was conducted. The purpose of this study was to find the differences in quality and quantity of metagenomic DNA extracted. The silica bentonite was compared to meet the Green Chemistry concept. The metagenomic DNA from these extractions were analyzed by agarose gel electrophoresis and UV-Vis spectrophotometry. The results of electrophoresis showed that metagenomic DNA extracted with silica bentonite were relatively higher in concentration than with phenol-chloroform-isoamyl alcohol; but integrity of their DNA were the same. The results of UV-Vis spectrophotometry analysis showed that A260/230 ratio of the phenol-chloroform-isoamyl alcohol extract had higher relative purity level to humic acid. The A260/280 ratio of the final elution of the silica bentonite extraction showed the highest relative purity level to protein.